The burden of non-communicable diseases among people living with HIV and the extent, cost and framework development of integrated HIV and non-communicable diseases care at primary health care facilities in Southern Africa - Musekiwa, Alfred (University of Pretoria, 2025)
Thesis (PhD (Public Health))--University of Pretoria, 2024.